(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Organisational Climate is the shared perception of an organisation’s environment and is a positive indicator of organisational performance. The performance and growth of various banks are dependent on the employees and work culture affecting prevalent organisational climate. This study aims to identify critical attributes of organisational climate affecting employee productivity of select bank groups. Survey questionnaires based on Organisational Climate Model (OCM) by Patterson et al., (2005) were administered to about 450 employees of 17 select banks divided into four groups of MNC, public, large and small private banks. Principle component analysis, confirmatory factor analysis and non-parametric correlations were performed as the data was not normally distributed. The analysis concluded that ten dimensions distributed in three sub-models of OCM positively affected productivity. Five dimensions of Human relations model and three of Rational goal model were most relevant. Two dimensions of Open systems model were also positively significant. MNC banks performed higher on employee productivity. Public sector banks fared least. The paper highlights vital attributes of organisational climate and significantly contributes to understanding factors affecting employee productivity in banks.